Union suppression and union substitution strategies of multinational enterprises in Ghana - Dayaram, Kantha; Ayentimi, Desmond; Burgess, John (Wiley-Blackwell, 2019)
This article complements the literature by furthering the understanding of an ‘African dimension’ of multinational enterprise (MNE) union avoidance. The evidence suggests that MNEs engaged in both union suppression and union substitution strategies by (i) exploiting young employees' apathy to promote opposition and indifference for union organisation (evil stuff), (ii) implementing union member‐centred employee retrenchment (fear stuff), (iii) using enterprise‐level collective bargaining arrangement to suppress union bargaining power (fear and fatal stuff), (iv) exploiting the fragmented labour union environment to suppress union organisation (fatal and evil stuff) and (v) promoting individual employee voice and involvement mechanisms (sweet stuff). Although MNEs in Ghana engaged in both union suppression and union substitution strategies, they appear to particularly favour the adoption of ‘union suppression’ strategies and what might be termed as ‘corridor tactics’. Our article highlights four transitional issues underpinning the emerging success of ‘corridor tactics’ in union suppression in a less developed host country.